Telaah Terhadap Alasan Memperingan Sanksi Pidana Dalam Putusan Mahkamah Agung Nomor 813/K/PID/2023 - Silviana Putri, Szyva; Adhari, Ade (UNES Law Review, 2024)
Considering Indonesia is a nation of laws, as stated in Article 1 paragraph (3) of the Constitution of 1945, the rule of law, not man, should govern the state. But when we examine this issue, we find that an authority figure who is meant to lead by example and safeguard the public is still negligent and has an insufficient comprehension of the law. A senior police officer can nevertheless be included in the "Whoever" part of Article 340 of the Criminal Code when it comes to organized murder proceedings because he acknowledges that the person being assaulted is a human being with legal status. This paper aims to examine the legal importance of prohibiting high-ranking police personnel from committing intentional murder as a type of official crime. This paper applies a normative legal research methodology that involves a statutory approach and a literature review. After the data is gathered, it is processed and given a descriptive explanation to allow for a factual explanation of the correlation between the data. The outcomes of the research lead to the conclusion that office crimes are covered by Article 52 of the Criminal Code and that offenders who hold senior police positions may face sanctions to discourage their actions and punish them for their accountability.